Emergency Laboratory Evaluations for Patients With Inborn Errors of Metabolism. Issue 12 (15th December 2021) - Gold, Nina B.; Kritzer, Amy; Weiner, Debra L.; Michelson, Kenneth A.
Abstract : Supplemental digital content is available in the text. Abstract : Background: Children with inborn errors of metabolism (IEM) are at risk for metabolic crises triggered by acute illnesses. Crises are identified through laboratory evaluations. Objectives: Our objective was to determine national adherence to minimum laboratory evaluations for patients with IEM in emergency departments (EDs), as well as factors associated with laboratory evaluation adherence. Methods: Using the Pediatric Health Information System, we identified visits to 48 EDs from 2012 to 2017 by children with IEM. We analyzed visits for catabolic conditions (dehydration, gastroenteritis, or vomiting) and determined variation in minimum laboratory evaluation adherence. Multivariable models were created to determine predictors of adherence. Results: Among the visits by children with disorders of the urea cycle, organic acid metabolism, and fatty acid oxidation, 1457 (76.3%) of 1909 adhered to the minimum laboratory evaluation. Median ED-level adherence was 78.2% (interquartile range, 67.4–92.5). Factors associated with adherence were disorder [fatty acid oxidation vs urea cycle disorder; adjusted odds ratio (aOR), 9.35; 95% confidence interval (CI), 4.07–21.47], annual ED volume of patients with IEM (quartile 4 vs 1; aOR, 3.58; 95% CI, 1.51–8.49), and presence of a biochemical genetics fellowship (aOR, 0.29; 95% CI, 0.14–0.62). Conclusions: Patients with IEM frequently did not receive minimum laboratory evaluations for catabolic conditions. Measures to improve laboratory use in children with IEM should be undertaken.